Displaced intrauterine contraceptive device: a prospective study at tertiary level hospital of Uttarakhand, India - Kumari, Nidhi; Gupta, Vineeta; Chaudhari, Priyanka; Nimonkar, Shweta; Tandon, Archna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The IUCD is a common method used for contraception. It is associated with complications like bleeding, perforation and migration to neighbouring organs as broad ligament, urinary bladder or omentum. Methods: A prospective study was carried out at SGRRIM and HS, Dehradun over a period of two years between January 2014 to December 2015. A total of 38 patients with a diagnosis of displaced IUCD were included for their detailed demographic profile, presenting complaints, required diagnostic and therapeutic modalities. Results: Ultrasound emerged as the preferred method to locate the displaced device. Majority of displaced IUCD were intrauterine (86.9%) and Hysteroscopy guided removal was the preferred method of removal regarding technique, safety, and cost and recovery time. Conclusions: Responsibility of care provider does not end at insertion of IUCD. Follow up is equally important. Every case of missing IUCD must be investigated carefully to rule out the possibility of uterine perforation.